A Chronicle of the Kentucky Transportation Research Program - Deen, Robert C. (1987)
The basis for the Kentucky Transportation Research Program (KTRP) was established more than 45 years ago and some of the current staff members have over 35 years experience in transportation research. Over the years, principal investigators have developed expertise in major areas of transportation and have made significant contributions in highway safety, pavement design and performance, embankment analyses, fatigue detection in bridges, noise abatement, traffic control and operations, voidless concrete, pavement texture and skid resistance, structural design and analyses of culverts, traffic forecasting, and numerous other areas. The Transportation Research Building houses several fully equipped laboratories. Special effort was made to provide flexibility and versatility in the arrangement of fixtures in the various laboratories. Computer services are available through the University of Kentucky and a full-time programming staff capable of summarizing, analyzing, and plotting data is available to all researchers. The Program also maintains a collection of current periodicals and publications from other transportation research organizations. Appreciable acceptance of study findings and resultant implementation of study recommendations has led to significant benefit-cost ratios for many studies undertaken by the unit. Values derived from research have been demonstrated routinely